Soybean sourdough as bio-ingredients to enhances physical and functional properties of wheat bakery products - Bustos, Ana Yanina (2017)
The aim of this work was to evaluate the strain Lactobacillus plantarum C8 as starter culture for soybean sourdough fermentation, in terms of rheological properties, phenolic content and antioxidant activity. After this, wheat breads were prepared with fermented (sourdough) and unfermented soybean flour (control) at three different ratios (4.0:1.0, 3.5:1.0 and 1.5:1.0). Soybean sourdough showed less consistency and increased viscosity compared with unfermented dough. The content of phenolic compounds and the antioxidant activity significantly (P < 0.05) increased after lactic fermentation. The overall characteristics of breads depended on the amount of soybean sourdough or flour addition while the best results were obtained with the lower substitution level. In fact, higher specific loaf volume, less crumb hardness and chewiness, and intensification in lightness with respect to control breads, were obtained. Besides, sourdough breads showed high phenolic content and antioxidant activity with respect to breads made with unfermented soybean flour. In addition, sourdough breads were widely accepted by the consumers. This work put in evidence that sourdough addition improved the physical and functional properties of traditional wheat bread.